Regional disparities in Ghana: Policy options and public investment implications - Al-Hassan, Ramatu M.; Diao, Xinshen (International Food Policy Research Institute, 2007)
The development pattern in Ghana is characterised by a north-south divide in which the north lags far behind the south... This paper sets out to identify avenues for pro-poor growth in Ghana, focussing on agricultural opportunities, particularly in northern Ghana. Using an economywide, multimarket model and based on time series production data between 1991 and 2000 and Ghana Living Standards Survey data of 1991/92 and 1998/99, this paper analyzes the possible poverty reduction trends up to 2015 by assuming different patterns of growth. The results show that agriculture-led growth has a larger poverty reducing effect than nonagriculture-led growth... A review of the literature shows that while the north generally is a net migration area, the rewards of migration have been limited because people who migrate have no skills and are, therefore, limited to entering the informal job market where wages are low. The implication is to enhance this labour with education and skills. Ultimately, the regions must attract production investment to boost economic activity and generate local growth. The state must play a leading role in investing in productive and social infrastructure as a way of facilitating the environment for private sector operators.